PENGARUH KURS DOLLAR AMERIKA SERIKAT, LUAS AREA BUDIDAYA, INDEKS HARGA PERDAGANGAN BESAR, JUMLAH PRODUKSI TERHADAP EKSPOR UDANG INDONESIA TAHUN 2000 - 2015 - Mayogantara, I Kadek Widnyana; Swara, I Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 10. Oktober 2017(pp.1868-2102), 2017)
The purpose of this research is to know how the influence of 4 economic factors are Shrimp Production, US Dollar Rate, Area, Large Trade Price Index (IHPB) to Indonesian Shrimp Export both simultaneously and partially. The data used in this study is secondary data with the period of 2000-2015. In analyzing the data used in this study is multiple linear regression using SPSS application program. The results of data analysis shows the amount of production, the United States dollar exchange rate, the area of ??cultivation and IHPB together significantly effect on shrimp exports from 2000 to 2015. Partially variable amount of production and area of ??cultivation have an insignificant effect on shrimp exports from 2000 to 2015 IHPB variables and US dollar exchange rate positively significant effect on shrimp exports 2000 - 2015. Variable production in this study dominant compared with other variables.